2018
DOI: 10.1097/cmr.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid aggregates in desmoplastic melanoma have features of tertiary lymphoid structures

Abstract: Desmoplastic melanomas (DM) have unique and challenging clinical presentations and histomorphology. A characteristic feature is the presence of scattered lymphoid aggregates. However, the nature of these aggregates is not defined. We hypothesized that they may be tertiary lymphoid structures (TLS), and may be associated with programmed death ligand 1 (PD-L1) expression. We searched our tissue database for 'pure' DMs and for scars as control tissues, collected clinical information, and reviewed H&E histology. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…CD45 + immune clusters surrounding PNAd + HEVs resembling bona-fide TLS 37 were identified as early as 5 days after initiating treatment with ADU S-100 ( figure 4B ). These therapy-induced TLS were richly infiltrated with CD11c + DCs and CD3 + T cells, resembling previously reported ‘non-classical’ TLS 38 ( figure 4C ). IFM analyzes did not, however, reveal significant B cell infiltrates in our specimens ( online supplemental figure S4B ); consistent with our observed lack of Cxcl13 expression in the TME of ADU S-100 treated animals ( figure 4A ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…CD45 + immune clusters surrounding PNAd + HEVs resembling bona-fide TLS 37 were identified as early as 5 days after initiating treatment with ADU S-100 ( figure 4B ). These therapy-induced TLS were richly infiltrated with CD11c + DCs and CD3 + T cells, resembling previously reported ‘non-classical’ TLS 38 ( figure 4C ). IFM analyzes did not, however, reveal significant B cell infiltrates in our specimens ( online supplemental figure S4B ); consistent with our observed lack of Cxcl13 expression in the TME of ADU S-100 treated animals ( figure 4A ).…”
Section: Resultssupporting
confidence: 88%
“…[59][60][61][62] Regardless of the ultimate role for B cells in a therapeutic TLS paradigm, it is noteworthy that in humans, the presence of either classical/mature or non-classical (ie, B-deficient) TLS in the TME correlates with improved patient outcome when compared with patients with tumors that fail to exhibit TLS. 38 While our studies were not specifically designed to identify mechanisms underlying resistance to i.t.-delivered STING agonist-based monotherapy that may have led to modest clinical activity in early-phase clinical trials, we observed that the treatment of DCs with ADU S-100 resulted in the compensatory upregulation of several known regulatory molecules that would be expected to mediate anti-inflammatory activity and thereby limit the therapeutic anti-tumor immune response. Notably, we observed that PD-L1, Ptgs2/COX2, Ptges and Arg2 expression were strongly upregulated on STING-activated DCs, suggesting these APCs may not mediate optimal/sustained immunostimulatory activity in vivo (online supplemental figure S6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The clinical impact of TLSs on responses to therapies has very recently been extended to other cancers and to immunotherapies (W.H.F., unpublished observations). It is interesting to note that a high proportion of desmoplastic melanomas exhibit TLSs 117 and that this tumour type also has a high response rate to PD1 blockade 118 .…”
Section: Correlation Between Tlss and Therapeutic Response In Patientsmentioning
confidence: 99%
“…We found that these foci of lymphoid populations were pronounced and focally involving skin appendages. In most of DM cases, these aggregates show features of tertiary lymphoid structures that contain a mixed type of cell population including organized clusters of usual CD20 + B‐cells and CD8 + T‐cells with CD83+ dendritic cells in T‐cell zones 24 . However, CLL is composed of monotonous, small‐sized neoplastic lymphoid cells with clumped chromatin that typically express CD5, CD11c, CD19 (dim), CD20 (dim), CD23, CD22 (weak or negative), Bcl‐2, and monoclonal kappa or lambda Ig light chain 25 .…”
Section: Discussionmentioning
confidence: 99%